2007
DOI: 10.1097/mnm.0b013e32828da1c7
|View full text |Cite
|
Sign up to set email alerts
|

A compartment model analysis for investigation of myocardial fatty acid metabolism in patients with hypertrophic cardiomyopathy

Abstract: Objective: The purpose of this study was to investigate the myocardial fatty acid metabolism in patients with hypertrophic cardiomyopathy (HCM) from dynamic SPECT through a compartment model analysis. Methods: Twenty-four normal controls, 7 patients with left ventricular hypertrophy (LVH) due to essential hypertension (eHT), and 30 patients with HCM were studied. I-123 BMIPP and Tc-99m tetrofosmin SPECT were performed. All the myocardium was divided into 13 segments, and totally 390 segments of HCM were catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Our work also corresponds to work by Okizaki et al [5]. Using dynamic SPECT imaging of 123 I-BMIPP, they showed that fatty acid metabolism was higher in patients with hypertrophic cardiomyopathy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our work also corresponds to work by Okizaki et al [5]. Using dynamic SPECT imaging of 123 I-BMIPP, they showed that fatty acid metabolism was higher in patients with hypertrophic cardiomyopathy.…”
Section: Discussionsupporting
confidence: 90%
“…In clinical settings, the abnormalities of fatty acid metabolism in hypertrophic cardiomyopathy can be recognized by the decreased uptake in single-photon emission computed tomography (SPECT) images [4]. It has also been demonstrated that compartmental analysis and dynamic SPECT imaging make it possible to detect abnormalities of fatty acid utilization earlier than SPECT imaging, with the potential to provide an even earlier prediction of the onset of cardiac hypertrophy [5]. There is a need to develop technology for imaging small animal models on clinical SPECT systems that could easily be translated to the clinic for diagnosis and management of patients with cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (41,48) have shown that myocardial uptake of free fatty acids, as measured by 123 Ilabeled 15-(p-iodophenyl)-3-(R,S)-methylpentadecanoic acid, is reduced in patients with HCM (41,48). Here, we demon- Fig.…”
Section: Abnormal Mitochondrial Fatty Acid Metabolism In the Hcm Heartmentioning
confidence: 99%
“…Table 2 compares the advantages and disadvantages of PET, MRS, and SPECT for quantification of myocardial metabolism. Despite these limitations, Okizaki et al were able to perform a compartment model analysis of myocardial fatty acid metabolism in patients with hypertrophic cardiomyopathy using SPECT with 123I-beta-methyl-iodophenylpentadecanoic acid (123I-BMIPP), a fatty acid analog and 99mTc-tetrofosmin perfusion radiotracer [29]. Using the myocardial and blood pool time-activity curves, 123I-BMIPP pharmacokinetics were analyzed through a two-compartment model.…”
Section: In Vivo Quantification Of Myocardial Metabolismmentioning
confidence: 99%